Remitting seronegative symmetrical synovitis with pitting oedema associated with chronic lymphocytic leukaemia - DİRESKENELİ, RAFİ HANER (SPRINGER VERLAG, 2000)
We describe a case of remitting seronegative symmetrical synovitis with pitting oedema (RS3PE syndrome) in a 67-year-old man. Immunophenotyping studies and histology of biopsy specimens revealed chronic lymphocytic leukaemia (CLL). Polyarthritis and oedema were revealed by small doses of corticosteroids. The association of RS3PE syndrome with rheumatological and malign disorders are discussed.
Keywords: chronic lymphocytic leukaemia; pitting oedema; RS3PE syndrome; EDEMA